BEBERAPA MASALAH COMMUNICATIVE TESTING DALAM PENDIDIKAN BAHASA lNGGRIS - Ferry Adenan (Jurnal Cakrawala Pendidikan, 2001)
Since 1945 English Language Education in Indonesia has been carried out according todifferent approaches and methods. These meet the needs of the era. English language teaching inIndonesia Iias experienced implementation according to the structural approach until thecommunicative approach at present. At the time when the structural approach was dominant, twosigtlificant method? were implemented, namely, the grammar-translation and the audiolingualmethod. The tests on English followed the methods that were implementedTests on Eilglish language education for the grammar-translation method differed from thosefor the audio linbml Translation, English composition writing, literary criticism, parsing exercises,and .language analyses were the test form given according to grammar-translation method whichwere characterized by uncontrolled subjective evaluation. G o d , valid, reliable, practical andobjective tests, statistical counts and indirect testing using multiple choice, true-false, matching anconlpletion as well as objective system of evaluation were carried out following the audio linguallnelhod.In the next development both the methods and' the forms of English Language testing lessfulfilled the standard of English mastery of learners in the era of globalization wherecommunication along nations of different countries happen very quickly because of the progressmade in the field of science and technology such as the invention of internet, E-mail, facsimile,became the creed of tile era lerefore, since 1994 the communicative approach in Englishlanguage education has been adopted. Integrative socio-linguistics, which is the basis of thecommur~icative approach, is predicted to arm the students with enough language competence to beable to paform commurrication in various situations and conditions in life. Communicative Ehglishlanguage tests appear to be very cornplex and difficult for tested as well as for test designers toconstmct. As an alternative solution to the problem, this article offers same approaches, techique,and procedures and steps in constructing the tests, accompanied by clear examples in the appendix.